2020
DOI: 10.1038/s41598-020-58709-w
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalytic activity of clean-surfaced, faceted nanocrystalline gold enhances remyelination in animal models of multiple sclerosis

Abstract: Development of pharmacotherapies that promote remyelination is a high priority for multiple sclerosis (MS), due to their potential for neuroprotection and restoration of function through repair of demyelinated lesions. A novel preparation of clean-surfaced, faceted gold nanocrystals demonstrated robust remyelinating activity in response to demyelinating agents in both chronic cuprizone and acute lysolecithin rodent animal models. furthermore, oral delivery of gold nanocrystals improved motor functions of cupri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…CNM-Au8 are a newly generated type of clean-surfaced gold nanocrystals with an average diameter of 13 nm which display high catalytic activity in primary rat neural-glia co-cultures. This was demonstrated by an enhanced expression of the redox coenzyme nicotine adenine dinucleotide (NAD+), increased intracellular levels of adenosine triphosphate (ATP), and an elevated extracellular lactate after administration of CNM-Au8 to cell cultures [68]. Treatment of OPC in vitro resulted in upregulation of differentiation and myelination pathways and significantly enhanced differentiation toward GalC-positive oligodendrocytes.…”
Section: Gold Nanocrystals (Cnm-au8)mentioning
confidence: 99%
“…CNM-Au8 are a newly generated type of clean-surfaced gold nanocrystals with an average diameter of 13 nm which display high catalytic activity in primary rat neural-glia co-cultures. This was demonstrated by an enhanced expression of the redox coenzyme nicotine adenine dinucleotide (NAD+), increased intracellular levels of adenosine triphosphate (ATP), and an elevated extracellular lactate after administration of CNM-Au8 to cell cultures [68]. Treatment of OPC in vitro resulted in upregulation of differentiation and myelination pathways and significantly enhanced differentiation toward GalC-positive oligodendrocytes.…”
Section: Gold Nanocrystals (Cnm-au8)mentioning
confidence: 99%
“…In contrast, a multiarm phase II trial in SPMS testing three different drugs with potential neuroprotective effects, amiloride, fluoxetine and riluzole, did not result in superior outcomes compared with placebo [162]. Ongoing studies include two trials examining the potential of nanocrystalline gold to treat remyelination failure and impaired neuronal redox state (NCT03993171, NCT03536559) [163].…”
Section: Regenerative and Neuroprotective Strategiesmentioning
confidence: 99%
“…Nanoparticles themselves can also act as remyelinating agents. Most recently, Robinson et al [64] reported a new nanocatalytic therapeutic candidate for remyelination, consisting of a suspension of clean-surfaced, faceted nanocrystals of gold, which was found to demonstrate robust remyelinating activity in response to demyelinating agents, in both chronic cuprizone and acute lysolecithin rodent animal models. More analytically, the administrated nanoparticles induced differentiation of OPCs and enhanced activities of neurons and oligodendrocytes through enhancement of bioenergetic processes of key indicators of aerobic glycolysis.…”
Section: Nanotechnology and Msmentioning
confidence: 99%